Injuriesagen mod Grundtvig 1825-1826 - Bøje, Grete (Grundtvig-studier, 1984)
The Libel Case against Grundtvig 1825-26 By Grete Bøje. In his search for a powerful argument against the rationalist understanding of Christianity Grundtvig underwent a long and complex cognitive process at the beginning of the 1820s; in July 1825 he came to the conclusion that the foundation of Christianity is the Apostles’ Creed.In mid-August 1825 Grundtvig, as a subscriber to the book, received a copy of H. N. Clausen’s The Church Constitution, Teaching and Ritual of Catholicism and Protestantism. Grundtvig saw the publication of this book of dogmatics as an admirable opportunity to promote his new understanding of Christianity and its foundations, and he therefore wrote The Church's Retort to the Professor of Theology, Dr. H. N. Clausen, in which he questioned the rationalist approach to Christianity and accused Clausen, among other things, of being a false teacher, claiming that the content of Clausen’s dogmatics was at odds with the constitution of the Danish State Church and its symbolical books.The Church's Retort was published only two days after Clausen’s book was advertised for sale, and it provoked a stormy debate, largely characterized by righteous indignation and scandal. Grundtvig could find noone to debate the serious theological and legal problems he had raised; Clausen was totally disinterested in any form of discussion of the case, and instead summonsed Grundtvig for libel.Grundtvig complained to the King about the summons, regarding his action as no more than the fulfilment of his clerical duties. But his complaint was rejected by the Chancellery and referred to the court’s jurisdiction.At Whitsun 1826 the Church was to celebrate its 1000-year anniversary in Denmark, and in March of that year a royal decree was published allowing the clergy the freedom to choose their own hymns for the anniversary services, provided O Mighty God, we sing Thy Praise (O, Store Gud, Vi love dig) was sung.Grundtvig understood the decree to mean that in their free choice of hymns the clergy were not even bound to the authorized hymnbook. He therefore wrote four hymns of celebration and had them printed in time for the anniversary service. However, the archdeacon at the Church of Our Lady in Copenhagen informed him that he was to stick to the authorized hymnbook. When Grundtvig wrote to the archdeacon to query this interpretation of the decree, the archdeacon reported him through Bishop Münter to the Chancellery, who in a further notice directed the clergy to stick to the authorized hymnbook.The King had had the palace chapel restored for the occasion, and Grundtvig had therefore written some poems in honour of the King. The week before the Whitsun festival Grundtvig sought an audience with the King to present the poems to him; during the audience it became clear to Grundtvig that the King regarded him as a libeller.All these factors, together with further threats regarding the libel case, resulted in Grundtvig feeling it necessary to offer his resignation. This was granted him - honourably - at the end of May. He then tried to discontinue the action through a private agreement with Clausen but was turned down flat. His next attempt was to use his resignation as an argument for not being judged for an action performed in the course of his clerical duties, from which he had now resigned. Grundtvig also maintained that by resigning he had voluntarily accepted a punishment for a possible offence. Both these arguments were rejected by Clausen and by the court.Meanwhile A. S. Ørsted published a series of articles in a legal journal on the degree to which the Danish State Church constitution needed changing, and as ill-luck would have it he took Clausen’s side in the libel case, a fact which Clausen naturally made use of in his address to the court. It goes without saying that Grundtvig was angered by this untimely vote against him, presented as it was by such a legal expert as Ørsted. In response Grundtvig wrote Important Questions for Denmark’s Jurists, condemning Ørsted’s reprehensible action and appealing yet again to the King to have the case stopped, but in vain.At the end of October Grundtvig was convicted of libel on the Royal Ordinance of September 27th 1799 concerning the limits to the freedom of the press; he was fined and sentenced to lifelong censorship. However, this was raised in December 1837.